Differences in Increasing Students' Communication Skills and Mathematical Problem Solving through Project-Based Learning with Virtual Manipulative and Physical Manipulative Media at SMP Plus Jabal Rahmah Mulia Medan - Evridya Rizki M; Ani Minarni; Waminton Rajagukguk (BIRCU, 2021)
This study aims to analyze the differences in the improvement of mathematical communication skills and mathematical problem solving of students who are taught using manipulative virtual learning media and physical manipulative learning through project-based learning models (PjBL), as well as analyzing the performance of class VII students of SMP Plus Jabal Rahmah Mulia Medan in solving problems. questions that measure communication skills and mathematical problem solving. Data obtained through subjective tests or essay tests, each of which measures the students' mathematical problem solving and communication skills. Data were analyzed using ANACOVA test. The population in this study were all students of class VIII of the private high school Jabal Rahmam Mulia for the 2020/2021 academic year. While the sample in this study is class VIII1 which is the first experimental class which is taught using manipulative virtual learning media and class VIII2 is the second experimental class which is taught using physical manipulative learning media. Based on the results of the ANACOVA calculation, the analysis results obtained F_hitung = 3,450 ˃ Ftable = 3.38 and with sig = 000, because the significant level is smaller than 0.05 so that H_0 is rejected and H_a is accepted. Thus, there are differences in problem-solving abilities between students who are given a realistic mathematics approach assisted by macromedia flash and students who are given a contextual approach assisted by macromedia flash. Based on the results of the analysis F_count = 20.889 ˃ F table = 3.38 and with sig = 000, because the significant level is smaller than 0.05 so that H_0 is rejected and H_a is accepted. Thus, there are differences in mathematical communication skills between students who are given virtual manipulative assisted project-based learning (PjBL VM) and students who are given physical manipulative assisted project-based learning (PjBL PM).